Waste Management Reform In Regions Of The Russian Federation: Implementation Issues On The Way To Sustainable Development - Andrei M. Dregulo; Alexander M. Khodachek (Geography, Environment, Sustainability, 2022)
Disposal of production and consumption waste is a worldwide problem. Despite the experience of foreign countries, waste disposal practice in the Russian Federation remains at the level of the 1970s. The method of waste burial at landfill sites prevails, leading to a loss of secondary resources and the appearance of sites of accumulated environmental damage, which is connected with the lack of a clear legal framework for waste management activities. Analysis of waste accumulation standards for apartment buildings in 20 regions of the Russian Federation showed that the difference in accumulation standards can vary by 2.32 times (from 0.125 m3 in the Kursk region to 0.279 m3 in the Voronezh region). At the same time, the difference in the cost of solid waste removal services can be varied by 2.74 times from 51.55 rubles in the Altai Territory (on average in the region) to 141.45 rubles in the Tyumen region. At the same time, the share of the population with incomes below the subsistence minimum in different regions reaches 7 - 36%. This is largely due to the critically low recovery of secondary materials (about 7%). The capacity of landfills in the regions of the European part of Russia (where more than 2/3 of the population lives) is almost exhausted. Many landfills of solid waste are objects of accumulated environmental damage. The decision to introduce the «institute» of “regional environmental operators”, which was adopted at the level of the Russian Federation to implement the waste management reform, has not, yet had any positive effect. Given the constant deficit of the consolidated budgets of most regions, the high level of poverty and the lack of state support, the prospects for waste management reform indicate the need for additional efforts on the part of the state, business and society.